Generational Inequalities in Argentina’s Working-Class Neighbourhoods - Vommaro, Pablo Ariel (2022)
The COVID-19 pandemic produced a generalized crisis that made visible pre-existing social dynamics. This chapter will focus on the multidimensional social inequalities, taking an intersectional approach, including the generational, gender, territorial and labour dimensions. I will shed light on young people from the barrios populares of Latin America’s urban centres. For this, I will mobilize some specialized literature available in a multidimensional and situated perspective (Vommaro, 2017b), considering the inequalities in the living conditions and the generational inequalities as constitutive features of contemporary Latin American youths (Vommaro, 2017a and 2019).